AGAINST SOCIAL STRATIFICATION IN OSCAR WILDE'S THE IMPORTANCE OF BEING ERNEST (1895): A MARXIST APPROACH - MURTININGRUM, LINDA DEWI (2010)
The object of the study is the drama script of The Importance of Being Ernest play written by Oscar Wilde. The study is to reveal how social stratification is reflected in The Importance of Being Ernest written by Oscar Wilde in 1895. The objective study is to analyze the structural elements in the play and to analyze the social stratification of the play based on Marxist Approach. The resacher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the dialouges, statements, and actions of The Importance of Being Ernest drama script and the secondary data sources is biography of character. The method of collecting data is note taking. The technique of analyzing data is descriptive. The result of the study is as follows. Firstly, based on the structural analysis, it is apparent that in this drama, Oscar Wilde conveys a moral message that social stratification and class status is not everything in life.Secondly, based on Marxist analysis, it is the evident that in this drama, Oscar Wilde reflects the social condition of Victorian people who tended to emphasize the social stratification.